2000
DOI: 10.1016/s0008-6363(00)00064-x
|View full text |Cite
|
Sign up to set email alerts
|

Injury current modulates afterdepolarizations in single human ventricular cells

Abstract: Our results demonstrate that I(injury) may either prevent or promote the occurrence of afterdepolarizations in human ventricle. The latter holds if conduction is slowed to such an extent that it permits flow of current from depolarized ischemic cells at plateau level to cells in phase 3 or phase 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
6
27
0
Order By: Relevance
“…3 Action potential shortening is an antiarrhythmic intervention for DAD-related arrhythmias. 4,11 In our study, the action potentials recorded from both rabbit and human myocytes were shortened by acute application of 3-PUFAs in both rabbit and human myocytes, except at fast (Ͼ2 Hz) stimulation rates ( Figure 3B). The shortening of the action potential by 3-PUFAs in human myocytes may have contributed to a reduced number of DADs.…”
Section: Fish Oil Shortens the Action Potential Durationssupporting
confidence: 49%
“…3 Action potential shortening is an antiarrhythmic intervention for DAD-related arrhythmias. 4,11 In our study, the action potentials recorded from both rabbit and human myocytes were shortened by acute application of 3-PUFAs in both rabbit and human myocytes, except at fast (Ͼ2 Hz) stimulation rates ( Figure 3B). The shortening of the action potential by 3-PUFAs in human myocytes may have contributed to a reduced number of DADs.…”
Section: Fish Oil Shortens the Action Potential Durationssupporting
confidence: 49%
“…4). This effect is comparable to previous studies, where real cells showing EADs were coupled to a passive RC circuit [11][12][13][14]. In our experiments, however, we additionally demonstrated that this occurs under conditions of failing as well as successful action potential propagation (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Eventually, the corresponding command potential V cmd is amplified and injected into the myocyte. This method was used to study, among others, the impact of depolarized, inexcitable cardiomyocytes in the ischemic tissue on the neighbouring cells (the so-called injury current; Verkerk et al 2000), or consequences of artificially implemented specific ionic current in cells where it is not naturally present (e.g. transient outward potassium current I to in guinea-pig or canine endocardial ventricular myocytes - Dong et al 2006).…”
Section: Model Clampmentioning
confidence: 99%